EDUKASI PIJAT KAKI RELAKSASI (PIJAR) DALAM UPAYA MENGONTROL TEKANAN DARAH DI WILAYAH KECAMATAN TAMBAK SARI - Iswati, Iswati; Orizani, Chindy Maria; Istifada, Rizkiyani; Susila, Wahyu Dini Candra (PPM STIKES Adi Husada, 2023)
Introduction & Aim: The aging process impacts reducing body resistance in older adults. Hypertension is a health problem caused by the aging process and lifestyle factors. The incidence of hypertension in older adults continues to increase in Surabaya. Non-pharmacological therapy with relaxing foot massage is an intervention to control blood pressure in older adults. Relaxing Foot Massage (PIJAR) educational activities in community service aim to increase the knowledge of older adults and their families in maintaining blood pressure. Method of Activity: Implementation of community service activities consists of three stages, such as initial survey, socialization, and implementation. Using a health education method, this activity was carried out on March 14, 2023, in Tambak Sari District, Surabaya. The material provided in this activity is the concept and demonstration of relaxing foot massage to 10 (ten) older adults and families. Data analysis used a univariate test with attention to the evaluation results through a questionnaire before and after health education. Results: There was an increase in knowledge after being given health education from 40% to 100% in good knowledge. There was an increase in average blood pressure from 40% to 60% after the Relaxation Foot Massage demonstration. Discussion: Health education and Relaxation Foot Massage can be used to increase the knowledge of the elderly group. Non-pharmacological therapy foot massage can help older adults to control blood pressure. Families have an active role in controlling blood pressure by providing relaxing foot massages to older adults.